Ultrastructural studies on bean leaf tissues infected with two strains of bean rugose mosaic virus - Kitajima, E.W.; Tascon, Angela; Gamez, R.; Galvez, G.E. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Electron microscopic studies of bean plant tissues (Phaseolus vulgaris L.) infected with races A, or A, of bean pod mottle mosaic virus (BRMV), isolated in Guatemala, showed conspicuous differences in their intracellular behavior with bean pod mottle virus (BPMV) and cowpea mosaic virus (CPMV) although they were serologically unrelated to these viruses.